The estimation of the hazard function of earthquakes in aceh province with likelihood approach - Maulidi, Ikhsan; Novika, Fanny; Mahmudi, Mahmudi; Apriliani, Vina; Syazali, Muhamad (Desimal: Jurnal Matematika, 2024)
In this article, we propose a novel application of the single decrement method with a likelihood approach to estimate the hazard function of earthquake events in Aceh province. While this method has traditionally been used in actuarial sciences for mortality table estimation, its application in seismic hazard estimation represents a new perspective in the field of earthquake risk analysis. To enhance the accuracy of the model, we applied the Box-Cox transformation to normalize the data and used simple regression to formulate the hazard function. Our results demonstrate that a cubic equation provides a more accurate model compared to linear and quadratic equations, as evidenced by the lower Mean Square Error (MSE). This study offers a new approach to hazard rate estimation that surpasses conventional methods by providing more informative and interpretable results for earthquake risk assessment.